KEPEMILIKAN SUMBER DAYA ALAM TERHADAP KONDISI SOSIAL EKONOMI WILAYAH DI INDONESIA - Atri Putri A; Zul Azhar; Joan Marta (Universitas Negeri Padang, 2015)
This study aims to determine the difference in life expectancy, the average, the difference in GDP per capita, and differences in poverty rates between developed regions rich natural resources and developed regions poor in natural resources. This study uses Typology Klassen in sampling, The results showed that there are significant differences in life expectancy in developed regions are rich in natural resources and advanced regions poor in natural resources. There are significant differences in the average length of school in the forward region rich in natural resources and advanced regions poor in natural resources. There are significant differences in GDP per capita between developed regions rich natural resources and developed regions poor in natural resources. There were no significant differences in the levels of poverty in the developed regions rich in natural resources with advanced regions poor in natural resourcesKeyword : natural resource curse, life expetancy, length of school, GDP, poverty